2011
DOI: 10.1186/1471-2229-11-99
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Ty3-gypsy group LTR retrotransposons Fatima on B-genome specificity of polyploid wheats

Abstract: BackgroundTransposable elements (TEs) are a rapidly evolving fraction of the eukaryotic genomes and the main contributors to genome plasticity and divergence. Recently, occupation of the A- and D-genomes of allopolyploid wheat by specific TE families was demonstrated. Here, we investigated the impact of the well-represented family of gypsy LTR-retrotransposons, Fatima, on B-genome divergence of allopolyploid wheat using the fluorescent in situ hybridisation (FISH) method and phylogenetic analysis.ResultsFISH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…(Suoniemi et al, 1996;Vicient et al, 1999), wheat (Charles et al, 2008;Salina et al, 2011) and pepper (Park et al, 2011(Park et al, , 2012b, have reported that the genomes expanded and were rearranged by accumulation of LTR-RTs. Our results suggest that LTR-RTs are also the main players in the enlargement and evolution of the ginseng genome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Suoniemi et al, 1996;Vicient et al, 1999), wheat (Charles et al, 2008;Salina et al, 2011) and pepper (Park et al, 2011(Park et al, , 2012b, have reported that the genomes expanded and were rearranged by accumulation of LTR-RTs. Our results suggest that LTR-RTs are also the main players in the enlargement and evolution of the ginseng genome.…”
Section: Discussionmentioning
confidence: 99%
“…This may be representative of heterochromatin structure adjacent to genic regions of the ginseng genome. The accumulation of LTR-RTs around genic regions has been reported in maize (SanMiguel et al, 1998;Kronmiller and Wise, 2009), wheat (Wicker et al, 2001;Salina et al, 2011), barley (Wicker et al, 2005) and pepper (Park et al, 2011(Park et al, , 2012b. In the pepper genome, accumulation of the Ty3/Gypsy elements such as Tat and Athila-like subgroups has resulted in expansion of euchromatic regions by random insertion (Park et al, 2011), while the Del-like subgroup has accumulated in constitutive heterochromatic regions such as pericentromeric regions (Park et al, 2012b).…”
Section: Pgdel and Remodeling Of Euchromatic Regions In The Ginseng Gmentioning
confidence: 99%
See 1 more Smart Citation
“…6 B, C). Other kinds of repetitive DNA, such as pSc119.2 [Badaeva et al, 1996;Molnár et al, 2014;present study] and different types of transposable elements [Raskina et al, 2004a[Raskina et al, , b, 2008Salina et al, 2009Salina et al, , 2011, could be the targets for nonhomologous/illegitimate recombination in virtually any area of the chromatin.…”
Section: Homologous and Nonhomologous Recombination Underlie Genotypementioning
confidence: 99%
“…The subgenome-specific LTR-RTs distribution was also discovered in other plants such as allopolyploid wheat (Sabot et al 2006;Salina et al 2011). In this study, we found another clue for allopolyploidization event in the ginseng genome.…”
Section: Amplification Of Ltr-rts During Ginseng Genome Evolutionmentioning
confidence: 53%